2022
DOI: 10.1108/ijhg-03-2022-0038
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the role of mobility restrictions in controlling COVID-19 outcomes: a regional level study of the Philippines

Abstract: PurposeThis paper aims to explore empirically the interactions between the coronavirus disease 2019 (COVID-19) pandemic, economic mobility and containment policy to test the effectiveness of mobility restrictions in controlling the spread of the disease.Design/methodology/approachThis study used weekly regional data for the 17 Philippine regions and estimated the effect of shocks using a panel vector autoregression (VAR) model.FindingsThe authors conclude that COVID-19 deaths and incidence primarily respond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Gaduena et al (2022) found that mobility restrictions have no or limited effect on virus transmission. Replicating their methodology in other settings would assist in answering the question as to whether this finding could be applied outside the research area.…”
Section: This Review Is Based On Gaduena a Caboverde Ce Flaminiano Jp...mentioning
confidence: 98%
See 4 more Smart Citations
“…Gaduena et al (2022) found that mobility restrictions have no or limited effect on virus transmission. Replicating their methodology in other settings would assist in answering the question as to whether this finding could be applied outside the research area.…”
Section: This Review Is Based On Gaduena a Caboverde Ce Flaminiano Jp...mentioning
confidence: 98%
“…Three articles deal specifically with topics around the COVID-19 pandemic. Gaduena et al (2022) examine the effect of mobility restriction on the spread of the COVID-19 virus in the Philippines. Surprisingly their conclusion argues that mobility restriction does not prevent viral transmission; this position is challenged by other authors, but read the article carefully before making your own mind up.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations